Perspective: Emergent magnetic phenomena at interfaces - Yuri Suzuki (APL Materials, 2015)
The discovery of emergent magnetic phenomena is of fundamental and technological interest. This perspective highlights recent promising examples of emergent ferromagnetism at complex oxide interfaces in the context of spin based electronics.